Culture and institutions : economic development in the regions of Europe - Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2005)
Does culture have a causal effect on economic development? The data on European regions suggest that it does. Culture is measured by indicators of individual values and beliefs, such as trust and respect for others, and confidence in individual self-determination. To isolate the exogenous variation in culture, I rely on two historical variables used as instruments: the literacy rate at the end of the XIXth century, and the political institutions in place over the past several centuries. The political and social history of Europe provides a rich source of variation in these two variables at a regional level. The exogenous component of culture due to history is strongly correlated with current regional economic development, after controlling for contemporaneous education, urbanization rates around 1850 and national effects. Moreover, the data do not reject the over-identifying assumption that the two historical variables used as instruments only influence regional development through culture. The indicators of culture used in this paper are also strongly correlated with economic development and with available measures of institutions in a cross-country setting.
Keywords: O10; P10; F10; N13; 330; culture; economic development; trust; literacy; institutions; Kultur; Regionale Entwicklung; Regionales Wachstum; Bildungsniveau; Schätzung; EU-Staaten